Stegosaurus the thoughtful surprise - Veitch, Catherine; Bakos, Barbara (Essex, England Miles kelly, 2019)
A Stegosaurus called Sonny and his family have recently moved to a new cave. Sonny is feeling quite sad and lost, so his dad comes up with a very thoughtful surprise to cheer him up
English stories
2
Keywords: Ankylosaurus -- Juvenile fiction; Dinosaurs -- Juvenile fiction; Friendship -- Jvuenile fiction